(untitled) (Publicaciones en Ciencias y Tecnología, 2023)
The analysis of the variation of carbon dioxide (CO2) emissions provides useful information for reduction alternatives. This study analyzed the effects of some determinants on CO2 emissions in the most representative sectors of Ecuador during the period 2000 - 2020, implementing the Logarithmic Mean Divisia Index (LMDI) methodology. The factors associated with CO2 emissions were analyzed, including carbon intensity, energy intensity, economic activity and population. Additive and multiplicative decomposition was applied to analyze the effects of the determining factors using an extension of the Kaya identity. The productive sectors with the greatest contribution to the interannual variation of CO2 emissions were identified. Economic income per capita and energy intensity were the factors that contributed most to emissions, while the carbonization index was the main factor in the reduction of CO2 emissions.